2012
DOI: 10.1021/nl301168r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxidation-Resistant Cupronickel Nanowires for Transparent Conducting Nanowire Networks

Abstract: Nanowires of copper can be coated from liquids to create flexible, transparent conducting films that can potentially replace the dominant transparent conductor, indium tin oxide, in displays, solar cells, organic light-emitting diodes, and electrochromic windows. One issue with these nanowire films is that copper is prone to oxidation. It was hypothesized that the resistance to oxidation could be improved by coating copper nanowires with nickel. This work demonstrates a method for synthesizing copper nanowires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
334
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(342 citation statements)
references
References 44 publications
4
334
1
3
Order By: Relevance
“…In the race to find better transparent electrodes, researchers have investigated numerous candidate materials 25,[38][39][40][41] . Figure 6a shows the transmittance versus sheet resistance of Li-intercalated ultrathin graphite as well as other high-performance transparent conducting materials, including other carbon-based materials 15,42 , and the best commercial indium tin oxide electrodes 40,43 .…”
Section: Resultsmentioning
confidence: 99%
“…In the race to find better transparent electrodes, researchers have investigated numerous candidate materials 25,[38][39][40][41] . Figure 6a shows the transmittance versus sheet resistance of Li-intercalated ultrathin graphite as well as other high-performance transparent conducting materials, including other carbon-based materials 15,42 , and the best commercial indium tin oxide electrodes 40,43 .…”
Section: Resultsmentioning
confidence: 99%
“…These methods prevent the CuNW surface from being exposed to oxygen by forming a passivation layer. Rathmell et al 17 reported the synthesis of the core-shell CuNWs, in which the core CuNWs were surrounded by a nickel shell in the form of cupronickel nanowires. However, the resistivity of such film was 3.1 times higher than pure CuNWs, due to the intrinsically higher resistivity of nickel.…”
Section: Introductionmentioning
confidence: 99%
“…We adopted and modified an electroless plating method for Power [mW] coating our CuNWs with nickel [25] . The details of the process are given in our experimental section.…”
Section: Resultsmentioning
confidence: 99%
“…The Ni-coating process is adopted from Rathmell et al [25] with some modification. Plasma-treated CuNW samples were placed in a beaker with 3 mL ethylene glycol.…”
Section: Ni-coated Cunw Thin Filmsmentioning
confidence: 99%